Morphological and molecular phylogeny of Epiperipatus (Onychophora: Peripatidae): a combined approach. Issue 3 (7th November 2020) - Costa, Cristiano S; Giribet FLS, Gonzalo; Pinto-Da-Rocha, Ricardo
Abstract: Onychophora, or velvet worms, are a key group for understanding ecdysozoan evolution. It comprises two families: Peripatopsidae, largely of Austral distribution, and Peripatidae, which is circumtropical. The interrelationships between the members of Peripatidae present many taxonomic issues exacerbated in the radiation of the Neotropical species or Neopatida. To understand the phylogeny of Neopatida, and to test the information of such morphological characters, we gathered novel molecular and morphological datasets focusing on Neotropical specimens. Our data were analysed using a combination of parsimony and maximum likelihood for the individual and combined molecular and morphological datasets. An analysis of morphology alone was inconclusive, supporting the notion that morphological characters used in peripatid taxonomy have little power to resolve phylogenetic relationships among higher taxa in Neopatida. However, the analyses of molecular or combined data show a split of the Neotropical species into two clades, which we use to reassign genera. Epiperipatus, as currently understood, is non-monophyletic, because it includes species of monotypic genera. To avoid paraphyly of Epiperipatus, the following new combinations are proposed: Epiperipatus bouvieri (Fuhrmann, 1913), Epiperipatus hitoyensis (Oliveira et al., 2012a), Epiperipatus solorzanoi (Morera-Brenes & Monge-Nájera, 2010) and Epiperipatus sucuriuensis (Oliveira et al ., 2015).